Estudo sobre a viabilidade de implementação de logística reversa e reciclagem de polímeros na indústria automobilística - Mietto, Luiz Henrique Milaré (Universidade Federal de São Carlos, 2023)
The present work consists of a bibliographical review on the topic of reverse logistics applied to the main polymers in the automotive industry. Reverse logistics is a process that aims to recover products, materials and components after use, with the aim of reintroducing them into the production cycle or using them for other purposes, such as recycling, energy generation or even the production of raw materials for the manufacture of new materials. The automotive industry is one of the most significant industries in Brazil, but it is also responsible for several environmental problems, including the generation of waste after automobile disposal. Of the waste generated, polymers stand out, which, when compared to other components and materials, have a lower rate of reuse. Thus, the implementation of reverse logistics of polymeric materials can contribute to reducing the environmental impact caused by industry, in addition to generating economic and social benefits. Among the main challenges faced in implementing reverse logistics in polymers in the automobile industry, the complexity of the supply chain, difficulty in adopting the recycling process, the lack of financial incentives and the need for investment in infrastructure and technology stand out. However, reverse logistics can bring several benefits to companies, such as reducing costs with purchasing raw materials, improving the company's image before consumers and society, developing new processes and technologies, and the generation of new business opportunities. To implement reverse logistics in polymers in the automobile industry, companies can adopt several strategies, such as recovering parts and components for reuse, recycling materials, remanufacturing products and selling waste to other companies. Therefore, the objective of this work is to base itself on well-established sustainability cases related to the automotive industry, such as the reverse logistics of tires and metal components, in the search for solutions aimed at the reverse logistics of polymers. With the results compiled by bibliographical research, it is concluded that there is the possibility of using a portion of recycled material in the manufacture of new components, and even the use of some polymers, mainly polyolefins, as an energy source. Simply implementing these practices would not solve the problem of reverse logistics in this industry, but they can serve as a starting point for future studies on this topic.
Study on the feasibility of implementing reverse logistics and polymer recycling in the automobile industry
Keywords: Logística reversa; Reciclagem; Polímeros; Indústria automobilística; Auto-peças; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA::MATERIAIS NAO METALICOS